Peran dan Implikasi Dewan Pengawas Syariah pada Lembaga Keuangan Mikro Syariah di Indonesia Perspektif Maqashid Syariah - Putri Meiliyawati; Alvien Septian Haerisma; Amir Amir (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2025)
Islamic cooperatives are financial institutions categorized as micro, operating based on Islamic Sharia principles. In carrying out its operations, Islamic cooperatives must ensure that all activities do not conflict with Sharia principles. The role of the Sharia Supervisory Board, as an extension of the DSN-MUI, is crucial in overseeing all cooperative activities. The purpose of this study is to determine the role of the sharia supervisory board and the implications for the realization of maqashid sharia in Kopsyah Harapan Sejahtera UIN Syekh Nurjati Cirebon. This research uses a qualitative method approach. The data collection techniques used were observation, interview, and documentation. The data sources used are primary and secondary data. The results showed that the role of the Sharia Supervisory Board of Kopsyah Harapan Sejahtera has been running optimally, because it has ensured that all cooperative activities and transactions, including fund management, products offered, and operations, are under sharia principles.